Efektifitas Penggunaan Media Video pada Pembelajaran Tematik Terpadu di Sekolah Dasar Saat Pandemi Covid-19 - Ridha, Mhd.; Firman, Firman; Desyandri, Desyandri (Jurnal Pendidikan Tambusai, 2021)
Learning media is an important factor in learning activities. Media becomes an intermediary between educators and students in delivering learning material.The outbreak of the Covid-19 pandemic in Indonesia has had a significant impact on Indonesian education. Educational activities carried out online from home. One of the learning media that is an alternative for educators during the Covid-19 pandemic is the use of video media. The purpose of this study was to see the extent to which video media was implemented in elementary schools during the Covid-19 pandemic based on the perspective of educators. The methodology used in this research is quantitative descriptive with an instrument in the form of a questionnaire distributed to elementary school educators in West Sumatra in December 2020. The results show that the implementation of learning during the Covid-19 pandemic using video learning media in elementary schools has been running smoothly. good. Learning video media was effectively implemented during the Covid-19 pandemic, because it made it easier for educators to teach material and made it easier for students to understand learning material.